Atypical Presentation of CLIPPERS Syndrome. Issue 3 (April 2015) - Gul, Maryam; Chaudhry, Ammar A.; Chaudhry, Abbas A.; Sheikh, Mubashir A.; Carsons, Steven
<x xml:space="preserve">Abstract</x> Abstract Numerous autoimmune diseases can affect the central nervous system (CNS), and variable clinical presentations confound the differential diagnosis. The challenging task of properly characterizing various CNS autoimmune diseases enables patients to be rapidly triaged and appropriately treated. In this review article, we aim to explore different CNS manifestations of rheumatologic diseases with emphasis on the utility of imaging and cerebrospinal fluid findings. We review the classic physical examination findings, characteristic imaging features, cerebrospinal fluid results, and serum biomarkers. In addition, we also present a unique case of newly described autoimmune entity CLIPPERS syndrome. Our case is unique in that this is the first case which demonstrates involvement of the supratentorial perivascular spaces in addition to the classic infratentorial involvement as initially described by Pittock et al (Brain. 2010;133:2626–2634).